Pembelajaran dengan Team Based Project untuk Meningkatkan Kemampuan Mahasiswa Merancang Eksperimen Fisika Berbasis Proyek - I Komang Werdhiana; Unggul Wahyono; Nurasyah Dewi Napitupulu; Yusuf Kendek (Jurnal Kreatif Online, 2023)
Learning that is carried out online has difficulty carrying out practicums with actual equipment. Because of that, another alternative is needed as a substitute for practicum. Substitute practicum can be done by providing projects that are carried out in a structured manner. The purpose of this study was to improve students' ability to design project-based physics experiments through team based project learning. This research was carried out by providing project assignments that were carried out in groups. Through this activity, we want to know the ability of students to design project-based physics experiments. The results of student projects were assessed by 5 Physics teachers using performance appraisal sheets. Assessment of student project results is carried out through focus group discussion activities. The results of the projects assessed are the results of the mid-semester and end-of-semester projects. The results of the assessment show that the results of the end-of-semester project get a higher score than the results of the mid-semester project. This means that through team based project learning, students can improve their ability to design project-based physics experiments.